AN ISLAMIC-SUPPORTED MODEL (MH4S MODEL) FOR WORK-LIFE BALANCE TOWARDS A HAPPIER LIFE - Ismael ABUJARAD; Mohamed Sulaiman; Ahmad, Khaliq; Othman, Abdul Kadir; Mohamed Noordeen Mohamed Imtiyaz (Journal of Islamic Management Studies, 2023)
Life is short-lived and within the short time we live, we always try to do things that we believe would make us happy. Thus, happiness in life is the goal that human beings try to achieve during their lifetime. Nevertheless, many people fail to achieve that goal of “being happy”. This could be due to misunderstanding what “happiness in life” or life contentment really means. Happiness in life, as proposed in this study, is not a life-related phenomenon. However, most people try to achieve happiness in life by focusing on life-related factors. Many people focus on their jobs as they believe success at work would make them happy. Others focus on their families as they believe happiness is felt because of family members’ life contentment. This paper argues that real happiness is not life driven. The authors believe that real happiness in life is felt when more focus is given to the life-after, not in the mundane and the temporary life itself. This paper proposes a model, known as MH4S Model, which is supported by Al Quran and Al Sunnah. This is the authors’ fervent belief that following this model could help people be happier at work, in their mundane lives in general and activities elsewhere. We define this model as Mind, Heart, Stomach, Gender Satisfaction (MH4S) Model. It proposes five components namely: Mind, Heart, Stomach, Sex desire /lust, self-satisfaction, and Soul. It states that enriching the mind and heart would lead to a positive contribution that increases self-esteem and self-satisfaction and thus makes the soul more positive while not eating much and staying away from lust would lead to higher self-esteem and higher level of spirituality.